Quality Management Concept in Higher Education - Tukiran Tukiran (Jurnal Pendidikan dan Konseling (JPDK), 2022)
Quality education is a necessity in the implementation of higher education and as one of the determinants for the development of the country. Quality graduates need a quality education system as well. In establishing a quality education system, in addition to human resources, facilities and infrastructure, curriculum and capital, quality management is also required. There are four areas of successful higher education management, such as: (1) students are satisfied with higher education services; (2) educational customers are satisfied with the service to their students; (3) shareholders are satisfied to have high-quality graduates who meet expectations; (4) lecturers and staff are satisfied with higher education services in several areas: division of labor, relations and communication between lecturers/leaders, employees, salary/honorarium received and services